2014
DOI: 10.1159/000368797
|View full text |Cite
|
Sign up to set email alerts
|

Relation of Indirect Vasodilator Use to Prognosis in Patients with Chronic Severe Mitral Regurgitation

Abstract: Objectives: The relation of indirect vasodilator use to cardiac events (CE) is undefined for chronic severe nonischemic mitral regurgitation (MR). The aim of this study was to resolve this knowledge deficiency. Methods: Data from 52 consecutive patients in our prospective natural history study with isolated chronic severe nonischemic MR were assessed post hoc over 19 years to examine the relation of indirect vasodilator use to subsequent CE (death or indications for valve surgery). At entry, no patient had sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
10
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 8 publications
3
10
0
Order By: Relevance
“…This uncertainty is reinforced by the observations of Supino et al [1], which are consistent with previous experiences with vasodilators in VHD. Prior experience in HF, especially in the V-HeFT trials, suggests that AB may be less effective in certain populations, just as was observed by Supino et al [1] in VHD.…”
Section: Angiotensin Blockers Versus Indirect Vasodilatorssupporting
confidence: 87%
See 4 more Smart Citations
“…This uncertainty is reinforced by the observations of Supino et al [1], which are consistent with previous experiences with vasodilators in VHD. Prior experience in HF, especially in the V-HeFT trials, suggests that AB may be less effective in certain populations, just as was observed by Supino et al [1] in VHD.…”
Section: Angiotensin Blockers Versus Indirect Vasodilatorssupporting
confidence: 87%
“…In fact, current guidelines for HF management recommend the routine use of nitrates, hydralazine and AB in the therapeutic regimen for appropriate patients with HF. It should be noted that other direct vasodilators, like minoxidil, and other indirect vasodilators, like prazosin, were not shown to be clinically effective in HF, analogous to the observations of Supino et al [1]. …”
Section: Direct Versus Indirect Vasodilatorssupporting
confidence: 69%
See 3 more Smart Citations